The acute effect of whole-body vibration on cycling peak power output - Fraser Hill, C. (Journal of Science and Cycling, 2013)
The aim of the present study was to determine if an acute bout of whole-body vibration (WBV) prior to sprint cycling would increase peak power output. Ten male cyclists, all familiar with maximal sprint cycling exercise performed, on two separate occasions, a ten second standing sprint on a cycle ergometer. For one trial the sprint was preceded by a 2 minute WBV intervention, requiring the participant to stand on a vibrating platform that produced sinusoidal oscillations. The frequency and amplitude of the vibration was set at 26Hz and `high` (approximately 2mm) respectively. For the other trial participants stood in the same position, however the platform did not vibrate (no-WBV; 0Hz and 0mm for frequency and amplitude respectively). No significant difference was recorded for peak power output between trials (1458.0 + 283.7 W versus 1506.3 + 232.5 W for WBV and no-WBV respectively, P = 0.17). The results suggest that WBV prior to maximal standing sprint cycling does not increase peak power output.